2005
DOI: 10.1289/ehp.8006
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafine Particles Cross Cellular Membranes by Nonphagocytic Mechanisms in Lungs and in Cultured Cells

Abstract: High concentrations of airborne particles have been associated with increased pulmonary and cardiovascular mortality, with indications of a specific toxicologic role for ultrafine particles (UFPs; particles < 0.1 μm). Within hours after the respiratory system is exposed to UFPs, the UFPs may appear in many compartments of the body, including the liver, heart, and nervous system. To date, the mechanisms by which UFPs penetrate boundary membranes and the distribution of UFPs within tissue compartments of their p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

36
745
6
12

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,208 publications
(824 citation statements)
references
References 39 publications
(45 reference statements)
36
745
6
12
Order By: Relevance
“…Fine particles (like CB) penetrate into cells by an endocytic process; however, the mechanism of ufCB uptake is still under debate. Results reported by Geiser et al (2005) suggested a mechanism that did not rely upon vesicle formation or an actin-based mechanism. As a consequence, the bioavailability of pollutants adsorbed onto particles of differing sizes must likely be different.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Fine particles (like CB) penetrate into cells by an endocytic process; however, the mechanism of ufCB uptake is still under debate. Results reported by Geiser et al (2005) suggested a mechanism that did not rely upon vesicle formation or an actin-based mechanism. As a consequence, the bioavailability of pollutants adsorbed onto particles of differing sizes must likely be different.…”
Section: Discussionmentioning
confidence: 98%
“…The size of particles determines the penetration into the cells (Geiser et al, 2005). Fine particles (like CB) penetrate into cells by an endocytic process; however, the mechanism of ufCB uptake is still under debate.…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of integrins suggests a potential of outside-in signaling following an interaction of the particles with extracellular structures of the membrane. However, nanoparticles have been described to enter the cell easily without using specific uptake mechanisms (16). It therefore may be speculated that the activation of the described pathway is triggered by intracellular processes comparable with the phosphorylation of EGF-R by intracellularly generated reactive oxygen species (32).…”
Section: Discussionmentioning
confidence: 99%
“…Nanosized particles are suspected to enter the human cells more easily than microsized particles (7), and ambient air-pollution particles smaller than 2.5 µm (PM2.5) have already been shown to be harmful to human health (8)(9)(10). The surface-to-volume ratio of nanoparticles is large, which may explain their high biological activity.…”
Section: Introductionmentioning
confidence: 99%